Essays on International Trade and Development - Benedikt Heid (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2014)
This volume was prepared by Benedikt Heid while he was working at the ifo Institute and the University of Bayreuth. It was completed in December 2013 and accepted as a doctoral thesis by the Department of Economics at the Ludwig-Maximilians-Universität München. It includes six self-contained chapters which deal with the following topics in empirical international trade and development economics: the expansion of firms' export destinations across space and time (chapter 1), the extension of structural gravity models for developed countries to include unemployment (chapter 2) and for Latin American and Caribbean developing countries to additionally include informal employment (chapter 3) as well as the relation between foreign direct investment, trade, and informal employment as illustrated by the maquiladora industry in Mexico (chapter 4), the interaction between migration and trade and their effects on unemployment (chapter 5), and the dynamics of democracy and income chapter 6).
Keywords: C23; C26; C33; D72; E21; F10; F20; O10; O17; O24; 330; Demokratie; Panelforschung; Export; Gravitationsmodell; Einkommen; Informeller Sektor; Außenhandel; Kosten; Internationale Wanderung; Auslandsverlagerung; Handelspräferenzen; Arbeitsmarkt; Arbeitslosigkeit; Export; Internationaler Markt; Räumliche Verteilung; Welt; Internationale Wirtschaft; Außenwirtschaftstheorie; Arbeitslosigkeit; Handelspräferenzen; Internationale Migration; Auslandsverlagerung; Schätzung; Welt; Nationaleinkommen; Demokratie; Demokratisierung; Schätzung; Welt